Simulator Kontrol Pengisian Calcium Carbonate (Caco3 ) dengan Sensor Ultrasonik Berbasis Mikrokontroler - Zainal Abidin (Universitas Islam Lamongan, 2019)
The problem in this study is to design the filling control of Calcium Carbonate CaCO3 using a microcontroller-based ultrasonic sensor and how to control charging Calcium Carbonate CaCO3 using an ultrasonic sensor based on a microcontroller. The purpose of this research is to find out the making of tools and work methods for filling Calcium Carbonate CaCO3 using an ultrasonic based microcontroller. In this study using qualitative research methods using data analysis in the field, the experiments with Ultrasonic Sensors HC-SR04, the working principle for detecting Calcium Carbonate CaCO3 with microcontrollers ATMEGA328. Components used: microcontroller, servo motor, LED, LCD, Photodioda. The results of this research test to find out how efficient, so that the filling control device of Calcium Carbonate CaCO3 with the HC-SR04 ultrasonic sensor can run well, testing is done with miniature trucks entering the filling area then ultrasonic sensors that have a value of 5 cm, the servo motor will opening the valve indicates charging is running. If filling in Calcium Carbonate CaCO3 which enters the truck is 50% volume, and Calcium Carbonate CaCO3 reaches a 9 cm height threshold from the Ultrasonic Sensor, the servo motor will move to cover the valve and the buzzer will ring indicating full charge.